Spectrum of Mutations in Pediatric Non-glomerular Chronic Kidney Disease Stages 2–5 - Wang, Xiaoyuan; Xiao, Huijie; Yao, Yong; Xu, Ke; Liu, Xiaoyu; Su, Baige; Zhang, Hongwen; Guan, Na; Zhong, Xuhui; Zhang, Yanqin; Ding, Jie; Wang, Fang (Frontiers in Genetics, 2021)
Renal hypodysplasia and cystic kidney diseases are the common nonglomerular causes of pediatric chronic kidney disease (CKD), and the diagnosis is usually based on the clinical and imaging characteristics. Whereas because of the high phenotypic heterogeneity, the correct final diagnosis of these two conditions is often depending on genetic testing. However, it is not clear whether the frequencies of damaged alleles vary among different ethnicities in children with nonglomerular CKD, which influences the strategy for genetic testing. In this study, a total of 69 unrelated children (40 boys, 29 girls) of predominantly Han Chinese ethnicity and with nonglomerular CKD stages 2-5 due to suspected renal hypodysplasia or cystic kidney diseases, were enrolled to perform molecular analysis using proband-only targeted exome sequencing and array-comparative genomic hybridization. Targeted exome sequencing found genetic etiologies in 33 patients (47.8%), covering 10 distinct genetic disorders. The clinical diagnoses in 13 of the 48 patients (27.1%) with suspected renal hypodysplasia were confirmed, and reclassified in 2 patients carrying mutations in nephronophthisis (NPHP) genes. The clinical diagnoses in 16 of the 20 patients (80%) with suspected cystic kidney diseases were confirmed, and reclassified in one patient with deletion of HNF1B. The diagnose of one patient with unknown nonglomerular disease was clarified. No CNVs were identified in the 20 patients with negative results of target exome sequencing. NPHP genes were the most common disease genes for the patients with onset at more than 6 years of age (14/45, 31.1%). The children with CKD stages 2 and 3 at onset were found to be caused by mutations in PAX2 and HNF1B genes (11/24, 45.8%), whereas those with CKD stages 4 and 5 were mostly caused by mutations in NPHP genes (19/45, 42.2%). The causative genes could not be indicated according to kidney imaging patterns at disease onset. Thus, our data showed in Chinese children with nonglomerular renal dysfunction due to renal hypodysplasia and cystic kidney diseases, the common causative genes vary with the age and CKD stage at disease onset, which will help to improve management and genetic counseling of these diseases in clinical practice.